7
$\begingroup$

I've encountered a curious identity as a codicil in some work. Is there a proof or reference?

$$\sum_{k=-n}^n\frac{2k+1}{n+k+1}\binom{2n}{n-k}\frac{x^k}{1+x^{2k+1}}=\frac{x^n}{1+x^{2n+1}}.$$

$\endgroup$
23
$\begingroup$

The $k=j-1$ and $k=-j$ terms cancel, so all that's left is the $k=n$ term.

| cite | improve this answer | |
$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.